Pathways and Pressures: Early Career Experiences in Aotearoa New Zealand’s Public Research Organisations - Ehau-Taumaunu, Hanareia; Forsdick, Natalie; Gobes, Emma; Hennessy, Louise; Cook, Michelle; Butowski, Nina; Morel, Jolin; Lynch, Courtney; Feltham, Grace; Mangan, Steph; et al. (New Zealand Science Review, 2026)
Public Research Organisations (PROs) are integral to the Science, Innovation and Technology (SI&T) sector in Aotearoa New Zealand, as mission-led organisations tied to research areas of significant national importance. Early career staff and students (ECS) make substantial contributions to delivering science impact within PROs, but face unique challenges, particularly amid prolonged sector-wide change. This manuscript is authored by the members of the Science New Zealand Early Career Member Group (ECMG), a cross-organisational body representing ECS from each of the PROs. As such, we are well-positioned to provide insight into the impacts of ongoing uncertainty for the PRO early career workforce. Drawing on data from a survey of early career staff and students across PROs conducted in December 2024, we highlight the impacts of the evolving SI&T landscape. Three key challenges emerged: ECS retention and career development, underrepresentation of Māori and Kaupapa Māori, and inequities in the current SI&T funding system. We discuss these challenges and offer solutions aimed at strengthening career pathways, supporting the growth and leadership of Māori ECS, and improving funding equity, which combined can enhance ECS success. Our ultimate goal is to help retain, develop, and empower the current and future early career cohort to thrive in their fields, delivering meaningful science impact for Aotearoa New Zealand.